The Narrative Value of Dance Communication: "habitus", musicality and emotion - Muntanyola, Dafne; Belli, Simone (Revista de Antropología Social, 2016)
The richness of dance comes from the need to work with an individual body. Still, the body of the dancer belongs to plural context, crossed by artistic and social traditions, which locate the artists in a given field. We claim that role conflict is an essential component of the structure of collective artistic creativity. We address the production of discourse in a British dance company, with data that spawns from the ethnography ‘Dance and Cognition’, directed by David Kirsh at the University of California, together with WayneMcGregor-Random Dance. Our Critical Discourse Analysis is based on multiple interviews to the dancers and choreographer. Our findings show how creativity in dance seems to be empirically observable, and thus embodied and distributed shaped by the dance habitus of the particular social context.